Traditional use and conservation of medicinal plants among Hehe society in Tanzania - Mkenda, Prisila; Mbilinyi, Gaston; Ligate, Elly; Mbago, Frank; Nyinondi, Onsemo Simon (Ethnobotany Research and Applications, 2025)
Background: The knowledge and use of medicinal plants are deeply rooted in the socio-cultural heritage of many African tribes. The study investigated the traditional use and conservation of medicinal plants among the Hehe community in Iringa, Tanzania, in response to increasing environmental pressure and demand for herbal remedies. Methods: The research was conducted in Mufindi and Kilolo districts during July 2022 and May 2023 through social surveys and field visits to document local medicinal plant species and conservation practices employed. Thirty key informants, including traditional healers, village leaders, and elders, were interviewed alongside twelve focus group discussions with youth, men, and women. Field visits, aided by a botanist, facilitated the identification of species mentioned during the surveys. Results: The study recorded 152 medicinal plant species across 61 families. Asteraceae and Fabaceae were the most represented families (16 species each), followed by Rubiaceae (12 species). An analysis of the IUCN Red List showed that most species were categorised as "Least Concern." However, Prunus africana was classified as "Vulnerable," and Warbugia ugandensis subsp. ugandensis, though unlisted, was noted as rare and heavily exploited. Leaves were the most used (44%), followed by roots (37%), stem bark (13%), fruits/seeds (3%), tubers (1%), and whole plants (2%). Trees were the most utilised (31%), followed closely by herbs (30%), shrubs (29%), climbers (7%), subshrubs (2%), and parasitic plants (1%). Traditional conservation practices employed were the use of sacred groves, spiritually guided harvesting, selective harvesting, and plant domestication. Conclusions: The findings underscore the rich ethnobotanical knowledge of the Hehe people and highlight the need for sustainable conservation of medicinal plant resources. Keywords: Traditional conservation, sacred groves, ethnobotany, Prunus africana, Warbugia ugandensis